Developing a Brief Tele-Psychotherapy Model for COVID-19 Patients and Their Family Members - Biagianti, Bruno; Zito, Silvana; Fornoni, Chiara; Ginex, Valeria; Bellani, Marcella; Bressi, Cinzia; Brambilla, Paolo (Frontiers in Psychology, 2021)
Objective: The COVID-19 pandemic is negatively impacting the mental health of COVID-19 patients and family members. Given the restrictions limiting in person contact to reduce the spread of the virus, a digital approach is needed to tackle the psychological aftermath of the pandemic. We present the development of a brief remote psychotherapy program for COVID-19 patients and/or their relatives. Methods: We first reviewed the literature on psychotherapeutic interventions for COVID-19 related symptoms. Based on this evidence, we leveraged ongoing clinical experiences with COVID-19 survivors and family members to design an intervention model that could be disseminated and integrated into the workflow of the mental health system. Results: This 8-session model –inspired by constructivist and hermeneutic-phenomenological therapies– serves COVID-19 patients during hospitalization, remission and recovery. This model can also be delivered to people dealing with the COVID-19 hospitalization/discharge of a family member, or the loss of a family member due to COVID-19. Conclusion: We described a remote psychotherapeutic approach to tackle the COVID-19 pandemic psychological aftermath. To date, the approach seems feasible and highly customizable to patients’ needs. Studies are underway to test its preliminary efficacy. Once proven efficacious, this treatment model could provide a blueprint for future tele-psychology wide-scale interventions.